Peterson’s algorithm Total correctness proof in IPCL - Zhygallo, A.A. (PROBLEMS IN PROGRAMMING, 2018)
The total correctness of the Peterson’s Algorithm has been proved. States and transitions were fixed by the program. Runtime environment considered is interleaving concurrency with shared memory. Invariant of the program was constructed. All reasoning provided in terms of Method for software properties proof in Interleaving Parallel Compositional Languages (IPCL). Conclusions about adequacy of the Method usage for such a kind of tasks (thanks to flexibility of composition-nominative platform) and its practicality as well as ease of use for real-world systems have been made based on this and other author’s works.Problems in programming 2016; 2-3: 113-118